Mesoporous cerium oxide nanospheres for the visible-light driven photocatalytic degradation of dyes - Muduli, Subas K (Beilstein-Institut, 2014)
A facile, solvothermal synthesis of mesoporous cerium oxide nanospheres is reported for the purpose of the photocatalytic degradation of organic dyes and future applications in sustainable energy research. The earth-abundant, relatively affordable, mixed valence cerium oxide sample, which consists of predominantly Ce(7)O(12), has been characterized by powder X-ray diffraction, X-ray photoelectron and UV–vis spectroscopy, and transmission electron microscopy. Together with N(2) sorption experiments, the data confirms that the new cerium oxide material is mesoporous and absorbs visible light. The photocatalytic degradation of rhodamin B is investigated with a series of radical scavengers, suggesting that the mechanism of photocatalytic activity under visible-light irradiation involves predominantly hydroxyl radicals as the active species.